Training women farmers on climate smart innovations in Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CCAFS East Africa together with partners facilitated the training of 130 women in the Nyando region on climate smart innovations. Focus areas included; new climate smart practices and agro-advisories, appropriate on farm tools and technologies and accessing microfinance and micro- insurance. The women interacted with a number of experts at the Agricultural Society of Kenya (ASK) Kisumu fair from 31 July to 3 August, 2013. Photos: V. Atakos.